AN OBSERVATIONAL STUDY ON MEDICATION ADHERENCE AND PREVALENCE OF COMPLICATIONS IN TYPE 2 DIABETES MELLITUS PATIENTS - VALAPARLA, GEETHA RANI; MADDI, PRANEETHA; VAKA, KALYAN BABU (International Journal of Current Pharmaceutical Research, 2021)
Objective: Diabetes is a complex heterogeneous disorder with chronic multiple illness which needs continuous medical management. Along with the medication life style modifications (diet, exercise) and patient self-management education is necessary not only for glyceamic control but also for prevention and delay of acute and long term complications. In this regard an observational study was carried out among 167 type 2 diabetic patients using a self-administered questionnaire in tertiary care hospital, Guntur. Methods: Patients of both genders in the age of 30-89 with co morbidities were included in the study. Data regarding social habits, medication and adherence, duration of diabetes, co-morbidities, presence of diabetic complications along with the prevalence of complications while practicing regular diet, exercise with medical adherence was collected and evaluated. Results: Among 167 patients 64.64 % were male and 35.36% were female. 14.4% of the populations are with diabetes from more than 17years. 65.3% of the patients don’t have alcoholic and smoking habit. Only 51.5% of the population was adherent to the medications. Hypertension is major co-morbidity existing among them. 82% of the study population reported macro vascular complication. The periodic prevalence rate(1-5years) of complications in type 2 diabetic patients who are adherent to medications and life style modifications was found to be 11.4% and the periodic prevalence rate of complications in patients who are either non-adherent to medications or life style modifications was 88.6%. Conclusion: Medical and life style adherence is strongly recommended which also must be promoted by conducting awareness programme and health care camps with continuous supervision by the family members over patients for healthy society.